"It often feels like you are talking to a wall": police and private security responses to the campaign to protect pont valley against opencast coal extraction - Griffin, Nathan Stephens (Critical criminology, 2021)
Conflict between police, private security and political protesters is a topic that has been researched widely in criminology and other disciplines (e.g., Choudry 2019; Gilmore et al. 2019; Goyes and South 2017; Jackson et al. 2018; Rigakos 2002; South 1988; Weiss 1978). Adopting a green criminological lens, this article seeks to contribute to this rich body of research by examining police and private security responses to campaigning against opencast (open-pit) coal mining in Pont Valley, County Durham, United Kingdom (UK). Based on qualitative interviews, the article examines activists’ perceptions of responses to their campaign. Our findings reveal that rather than acting as neutral arbiters, police colluded with private interests, overlooking the abusive behavior of private security and bailiffs, particularly during the eviction of a protest camp at the proposed mining site. Activists believed that their right to protest was not respected, that their safety was jeopardized, and that police had willfully ignored a wildlife crime perpetrated by the mining company in order to enable mining to go ahead. Our article argues that the Pont Valley case fits into a wider pattern of repression of environmentalism in the UK, supporting Gilmore and colleagues’ (2019) argument that a progressive transformation in policing has been overstated.